2017
DOI: 10.5137/1019-5149.jtn.19263-16.2
|View full text |Cite
|
Sign up to set email alerts
|

One-stage posterior approach in the treatment of consecutive multi-segment thoracic tuberculosis with kyphosis

Abstract: The one-stage posterior approach of debridement and drainage is a feasible surgical option for consecutive multisegment thoracic tuberculosis with kyphosis. It can achieve debridement, decompression, and stabilization simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This treatment strategy can achieve complete debridement, ensure bone graft fusion efficacy, reduce the probability of the infection spreading, correct kyphosis, and prevent the progressive worsening of kyphosis after surgery [1, 3, 4]. However, this surgical strategy greatly increases the operative time, blood loss volume, surgical trauma, and incidence of perioperative complications [57]. In recent years, it has been reported that in cases of progressive single-segment spinal tuberculosis, surgery by a posterior approach can achieve complete debridement, decompression, bone fusion, and internal fixation and can effectively correct spinal kyphosis, which has the advantages of mild trauma, few perioperative complications, low cost, and short recovery time[8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…This treatment strategy can achieve complete debridement, ensure bone graft fusion efficacy, reduce the probability of the infection spreading, correct kyphosis, and prevent the progressive worsening of kyphosis after surgery [1, 3, 4]. However, this surgical strategy greatly increases the operative time, blood loss volume, surgical trauma, and incidence of perioperative complications [57]. In recent years, it has been reported that in cases of progressive single-segment spinal tuberculosis, surgery by a posterior approach can achieve complete debridement, decompression, bone fusion, and internal fixation and can effectively correct spinal kyphosis, which has the advantages of mild trauma, few perioperative complications, low cost, and short recovery time[8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…In the studies by Jia et al, 10 the mean age of presentation was 45.9 ± 12.7 years, with a range of 27 to 69 years. The mean age of representation in the studies by Zhong et al 11 was 45.5 years, with a range of 19 to 76 years. Dai et al 12 in their studies found that the mean age of presentation of the disease was 43.8 ± 12 years, with an age range of 25 to 68 years.…”
Section: Discussionmentioning
confidence: 87%
“…With advancements in the posterior technique, some surgeons have begun to use posterior-only surgery to treat multisegment thoracic TB. Zhong et al [ 20 ] and Wu et al [ 21 ] treated TB patients with multisegment lesions and kyphosis by posterior-only surgery, and all patients were cured and had no recurrence of TB. For multisegment thoracic and lumbar TB, posterior surgery can be performed with multisegment transforaminal and paravertebral approaches according to the type of lesion; in some indirect operations, the lesion surrounding the spine can be effectively cleared, and the case of TB can be cured [ 22 ].…”
Section: Discussionmentioning
confidence: 99%